The Effect of Financial Performance on Profit Growth Moderated by CSR Disclosure - NIKMAH, ULFATUN; Fajarini, Indah (Universitas Negeri Semarang, 2020)
Profit growth is one of the indicators used by stakeholders to know the company’s financial performance before. The high-profit growth represents that financial performance is well. The emergence of the obligation to disclose Sustainability Reporting including CSR affects financial performance and profit growth. This study intended to know the effect of financial performance on profit growth moderated by CSR disclosure. Financial performance was measured by using Net Profit Margin (NPM), Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER). The population was 42 consumer goods industry sector companies registered on the Indonesia Stock Exchange from 2014 to 2016. The study used purposive sampling method and obtained 75 analysis units from 15 companies with 5 years of observation. The data analysis technique used moderating regression analysis with SPSS. The study showed that NPM had a significant positive effect on profit growth, whereas ROE, CR, and DER did not. CSR could moderate the effect of NPM, ROE, and DER to profit growth, but it could not moderate the effect of CR to profit growth. The conclusion was CSR disclosure proven to strengthen financial performance on profit growth. Keywords: Corporate Social Responsibility; Current Ratio; Debt to Equity Ratio; Net Profit Margin; Profit Growth; Return on Equity